EFFECTS OF VARIATION IN UMBILICAL ARTERY RESISTIVE INDEX ON PLACENTAL MORPHOLOGY AND BIRTH WEIGHT IN PREGNANCY INDUCED HYPERTENSION - Borges, Kevin Joseph Jerome; Hassan, Nuzhat; Hussain, Rubina; Akhtar, M. Tameem (Journal of Ayub Medical College Abbottabad, 2013)
Background: Pregnancy induced hypertension results from defective trophoblast invasion and increased umbilical artery resistance which in turn results in decreased blood supply to the placenta and hence to the foetus. This arterial resistance varies in different cases of PIH thus causing variable effects on placenta and foetus. The objective of this study was to study the morpho-metric changes in placenta and alterations in birth weight with differences in umbilical artery resistive index in hypertensive pregnancies. Methods: Ninety pregnant women with pregnancy induced hypertension were selected with gestational age greater than 35weeks. Doppler ultrasound examinations were carried out to record umbilical artery resistive index (UARI). 2 groups were made on the basis of median values of UARI. Plain ultrasound examination was then carried out to record presentation, site of placentation, grade of maturity, insertion of the cord, cord thickness, placental thickness, vacuolation and amniotic fluid index (AFI). After delivery, foetal birth weight was noted and placentae examined for placental weight, infarcts, number of cotyledons, umbilical cord insertion, cord thickness and placental thickness were noted. Foeto-placental weight ratio was also calculated. Results: Significantly higher UARI was seen in the high-resistance group. Significantly lower values of placental thickness, AFI, birth weight, placental weight and placental thickness, whereas greater number of grade-III maturity, infarcts and marginal cord insertion were noted in the high-resistance group. Conclusion: Increased UARI leads to a spectrum of changes in the placenta and also decreased birth weight. Marginal cord insertion causes greater risk of increased UARI. Keywords: PIH, Umbilical Artery, Resistive Index, Placenta